Phosphatidylserine in the brain: Metabolism and function - Kim, Hee-Yong; Huang, Bill X.; Spector, Arthur A. (Progress in lipid research, 2014)
Phosphatidylserine (PS) is the major anionic phospholipid class particularly enriched in the inner leaflet of the plasma membrane in neural tissues. PS is synthesized from phosphatidylcholine or phosphatidylethanolamine by exchanging the base head group with serine, and this reaction is catalyzed by phosphatidylserine synthase 1 and phosphatidylserine synthase 2 located in the endoplasmic reticulum. Activation of Akt, Raf-1 and protein kinase C signaling, which supports neuronal survival and differentiation, requires interaction of these proteins with PS localized in the cytoplasmic leaflet of the plasma membrane. Furthermore, neurotransmitter release by exocytosis and a number of synaptic receptors and proteins are modulated by PS present in the neuronal membranes. Brain is highly enriched with docosahexaenoic acid (DHA), and brain PS has a high DHA content. By promoting PS synthesis, DHA can uniquely expand the PS pool in neuronal membranes and thereby influence PS-dependent signaling and protein function. Ethanol decreases DHA-promoted PS synthesis and accumulation in neurons, which may contribute to the deleterious effects of ethanol intake. Improvement of some memory functions has been observed in cognitively impaired subjects as a result of PS supplementation, but the mechanism is unclear.